PENGARUH MODEL PEMBELAJARAN PENCAPAIAN KONSEP (CONCEPT ATTAINMENT) TERHADAP HASIL BELAJAR SISWA PADA MATERI POKOK PENGUKURAN - Nainggolan, Andi Putra; Derlina, Derlina (JURNAL IKATAN ALUMNI FISIKA, 2017)
This study was aimed to know the effect of the The concept Attainment model of student learning outcomes in the measurement of the material. This research is a quasi-experimental. Sampling was done by cluster random sampling by taking two classes at random that the experimental class and control class. The instrument used was a test of learning outcomes and learning activities. treatment with an experimental class given The concept Attainment model and grade control with conventional learning. The results of this study indicate that the application of The concept Attainment model can increase the average value of each meeting learning activities and student learning outcomes in the subject matter of measurement.